Information Model for Non-Formal Education Management in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The  study aim to develop and to evaluate information model for educational management in non-formal education in Thai supply chain. The sample groups were three experts in supply chain management, three experts in Information and technology and four experts in curriculum. The research tool was evaluation form to  evaluate information model for educational management in non-formal education in Thai supply chain comprises five main components, namely Raw materials, Supplier,   Manufacturer education  , Finished product and Customers. The data analysed by using arithmetic mean and standard deviation information model for educational management in non-formal education in Thai supply chain using Back-Box technique. The results from experts have evaluated the model and commented that the model is high level of appropriateness, suggesting that information model to support sustainable   information development.